Molecular vasculogenic mimicry–Related signatures predict clinical outcomes and therapeutic responses in bladder cancer: Results from real-world cohorts - Zhang, Chunyu; Xiao, Jiatong; Yuan, Tong; He, Yunbo; Deng, Dingshan; Xiao, Zicheng; Chen, Jinbo; Zu, Xiongbing; Liu, Peihua; Liu, Zhi (Frontiers in Pharmacology, 2023)
Bladder cancer (BLCA) is a heterogeneous disease, there are many classical molecular subtypes that reflect TME heterogeneity, but their clinical utility is limited, and correct individual treatment and prognosis cannot be predicted based on them. To find a reliable or effective biomarkers or tools for predicting patients' clinical responses to several therapies, we developed a new systemic indicator of molecular vasculogenic mimicry (VM) related genes mediated by molecular subtypes based on the Xiangya cohort and additional external BLCA cohorts using a random forest algorithm. A correlation was then done between VM_Score and classical molecular subtypes, clinical outcomes, immunophenotypes, and treatment options for BLCA. With VM_Score, it is possible to predict classical molecular subtypes, immunophenotypes, prognosis and therapeutic potential of BLCA with high accuracy. VM_Scores of high levels indicate a more anticancer immune response but a worse prognosis due to a more basal and inflammatory phenotype. VM_Score was also associated with low sensitivity to antiangiogenic and targeted therapies targeting the FGFR3, β-catenin and PPAR-γ pathways, but high sensitivity to cancer immunotherapy, neoadjuvant chemotherapy and radiotherapy. A number of aspects of BLCA biology were reflected in the VM_Score, providing new insights into precision medicine. Additionally, VM_Score may be used as an indicator of pan-cancer immunotherapy response and prognosis.